2021
DOI: 10.1084/jem.20201637
|View full text |Cite
|
Sign up to set email alerts
|

A TRPA1 inhibitor suppresses neurogenic inflammation and airway contraction for asthma treatment

Abstract: Despite the development of effective therapies, a substantial proportion of asthmatics continue to have uncontrolled symptoms, airflow limitation, and exacerbations. Transient receptor potential cation channel member A1 (TRPA1) agonists are elevated in human asthmatic airways, and in rodents, TRPA1 is involved in the induction of airway inflammation and hyperreactivity. Here, the discovery and early clinical development of GDC-0334, a highly potent, selective, and orally bioavailable TRPA1 antagonist, is descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 103 publications
5
74
1
Order By: Relevance
“…Drug discovery efforts have been hampered by the limited bioavailability of TRPA1 antagonists 167 , 168 . Recently, a potent, selective and orally bioavailable small molecule TRPA1 antagonist, GDC-0334, with good target engagement in human volunteers, has been reported 169 . In preclinical models of respiratory disease, GDC-0334 inhibited cough response, airway smooth muscle hyperreactivity and oedema formation in several species 169 .…”
Section: Respiratory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Drug discovery efforts have been hampered by the limited bioavailability of TRPA1 antagonists 167 , 168 . Recently, a potent, selective and orally bioavailable small molecule TRPA1 antagonist, GDC-0334, with good target engagement in human volunteers, has been reported 169 . In preclinical models of respiratory disease, GDC-0334 inhibited cough response, airway smooth muscle hyperreactivity and oedema formation in several species 169 .…”
Section: Respiratory Diseasementioning
confidence: 99%
“…Recently, a potent, selective and orally bioavailable small molecule TRPA1 antagonist, GDC-0334, with good target engagement in human volunteers, has been reported 169 . In preclinical models of respiratory disease, GDC-0334 inhibited cough response, airway smooth muscle hyperreactivity and oedema formation in several species 169 . It is hoped that clinical studies with GDC-0332 (or other compounds with good bioavailability) will answer the question of whether blocking TRPA1 in respiratory disorders has therapeutic promise 168 .…”
Section: Respiratory Diseasementioning
confidence: 99%
“…NCA analysis showed that GDC-0334 exhibited linear PK with a mean t 1/2 greater than 9 days, and we observed accumulations in exposure following repeat dosing, consistent with our preclinical observation in dogs. 8 F I G U R E 2 Observed pharmacokineticpharmacodynamic (PK-PD) relationship from the clinical study demonstrates the inhibition of allyl isothiocyanate (AITC)induced dermal blood is dose proportional to the plasma concentrations of GDC-0334. DBF, dermal blood flow; AUC 0-10 min , area under the curve from time 0 to 10 min; SCR, baseline data from screening period; SAD, single ascending dose; MAD, multiple ascending dose; ss, steady state; solid black line, nonlinear regression curve fit line.…”
Section: Discussionmentioning
confidence: 99%
“… 8 The absorption, distribution, metabolism, and excretion properties of GDC‐0334 based on in vitro and preclinical in vivo studies were described previously. 8 …”
Section: Methodsmentioning
confidence: 99%
“…These findings indicate that neuronal TRPA1 is critical in asthmatic inflammation. Recent preclinical studies showed that TRPA1 blockage with a small molecule inhibitor GDC-0334 suppressed inflammation and airway smooth muscle contraction [ 88 ]. Instead of direct blockage of the immunologic factors mediating asthma pathogenesis, alternative approaches targeting pathogenic factors, such as those involved in neurogenic inflammation in asthma, hold great potential for the treatment of Th2-low asthma.…”
Section: Biological Therapies Under Clinical Trialsmentioning
confidence: 99%